Emerging Trends and the Way Forward in Design in Healthcare: An Expert's Perspective. (28th July 2017) - Tsekleves, Emmanuel; Cooper, Rachel
Abstract: In this paper the authors provide a new perspective on the emerging trends and way forward for design in healthcare. The article is based on an analysis of 20 chapters and 26 case studies contributed by design research experts for an international book in Design for Health (currently in press1) edited by the authors. The paper aim is to provide design researchers, with an interested in health, with new insights. Focusing on the five identified emergent trends in design for healthe the authors discuss how designers can contribute to different dimensions of health (in public, acute, chronic healthcare and in ageing well), as dictated by several of the healthcare challenges and opportunities created by design research and the advent of digital technology. The analysis reveals that design has the capacity to contribute significantly to future healthcare. It has also revealed that the key agenda going forward and requiring immediate attention is that of preventative healthcare.